Identification of pharmacological agents that induce HMGB1 release. Issue 1 (December 2017) - Liu, Peng; Zhao, Liwei; Loos, Friedemann; Iribarren, Kristina; Lachkar, Sylvie; Zhou, Heng; Gomes-da-Silva, Lígia; Chen, Guo; Bezu, Lucillia; Boncompain, Gaelle; Perez, Franck; Zitvogel, Laurence; et al.
Abstract The translocation of the protein high mobility group box 1 (HMGB1) from the nucleus to the cytoplasm and its secretion or passive release through the permeabilized plasma membrane, constitutes a major cellular danger signal. Extracellular HMGB1 can interact with pattern recognition receptors to stimulate pro-inflammatory and immunostimulatory pathways. Here, we developed a screening assay to identify pharmacological agents endowed with HMGB1 releasing properties. For this, we took advantage of the "retention using selective hooks" (RUSH) system in which a streptavidin-NLS3 fusion protein was used as a nuclear hook to sequestrate streptavidin-binding peptide (SBP) fused with HMGB1 and green fluorescent protein (GFP). When combined with biotin, which competitively disrupts the interaction between streptavidin-NLS3 and HMGB1-SBP-GFP, immunogenic cell death (ICD) inducers such as anthracyclines were able to cause the nucleo-cytoplasmic translocation of HMGB1-SBP-GFP. This system, was used in a high-content screening (HCS) campaign for the identification of HMGB1 releasing agents. Hits fell into three functional categories: known ICD inducers, microtubule inhibitors and epigenetic modifiers. These agents induced ICD through a panoply of distinct mechanisms. Their effective action was confirmed by multiple methods monitoring nuclear, cytoplasmic and extracellular HMGB1 pools, both in cultured human or murine cells, as well as in mouse plasma.